FRI0236 FIRST PILOT STUDY OF T1 MAPPING MRI WITH ECV MEASUREMENT OF PERIPHERAL MUSCLE IN SYSTEMIC SCLEROSIS PATIENTS SHOWS DIFFUSE FIBROSIS. (2nd June 2020) - Dumitru, R. B.; Goodall, A.; Broadbent, D.; Kidambi, A.; Plein, S.; Del Galdo, F.; Tan, A. L.; Biglands, J.; Buch, M. H.
Abstract : Background: Peripheral myositis in systemic sclerosis (SSc) is associated with poor prognosis and myocarditis 1 but non-inflammatory myopathy, which also represents a significant cause of disability in SSc remains poorly understood. Cardiovascular magnetic resonance (CMR) T1 mapping studies in asymptomatic SSc patients show increased extracellular volume (ECV), suggestive of diffuse fibrosis in both the myocardium and thoracic muscle 2 . Objectives: To evaluate the feasibility of T1 mapping MRI and determine ECV in peripheral muscle of SSc patients with and without myopathy and explore the association between cardiac and peripheral muscle T1 mapping in SSc. Methods: This was a hypothesis-generating pilot and feasibility study. SSc patients, fulfilling the 2013 ACR/EULAR criteria, with no cardiovascular disease or myositis but either minimal muscle symptoms (non-inflammatory myopathy) or no muscle involvement and healthy volunteers (HV) underwent peripheral muscle T1 mapping-MRI for native T1 and extracellular volume (ECV) quantification of the dominant thigh. Patients also had T1 mapping CMR, and creatine-kinase (CK) measured. Non-inflammatory myopathy was defined as current/history of minimally raised CK (<600 IU/l) +/- presence of clinical signs-symptoms (including proximal myasthenia and/or myalgia) +/- a Manual Muscle Testing (MMT) score <5 in the thighs. Results: 12 SSc patients and 10 HV were recruited. SSc patients had a median (IQR) age of 52 (41, 65) years, 9/12 had limited cutaneous SSc, 4/12 interstitial lung disease, 7/12 non-inflammatory myopathy. Higher skeletal muscle ECV was recorded in SSc patients compared to HV [mean (SD) 23(11)%, vs 11(4)% p=0.04]. Skeletal muscle native T1 values were comparable between the 2 groups although modestly higher in SSc patients [mean (SD) 1396ms (56) vs 1387ms (42)] (Figure 1A ). Peripheral muscle ECV associated with CK (R 2 =0.307, rho=0.554, p=0.061) and was higher in SSc patients with evidence of myopathy compared to those with no myopathy [28 (10)% vs 15 (5)%, p=0.023] (Figure 1B ). An ECV of 22% was determined to best identify myopathy with a sensitivity of 71% and a specificity of 80%. SSc patients had raised myocardial ECV and native T1 with means (SD) of 31 (3) % and 1287 (54) ms respectively (normal reference range ECV ≤29%, native T1 ≤1240ms). No clear association between myocardial and peripheral muscle ECV (rho=-0.485) or between myocardial ECV and peripheral muscle native T1 (rho=0.470) of SSc patients was observed. Conclusion: This pilot study to determine ECV-MRI of the peripheral muscle showed higher ECV in SSc patients compared to HV, suggesting the presence of diffuse fibrosis in the peripheral muscle of SSc patients. These data support further investigation to understand the pathophysiological involvement and relationship of peripheral and cardiac muscle in SSc. References: [1]Follansbee WP et al, Am Heart J. 1993 [2]Barison A et al, Eur Heart J Cardiovasc Imaging. 2015 Disclosure of Interests: Raluca-Bianca Dumitru: None declared, Alex Goodall: None declared, David Broadbent: None declared, Ananth Kidambi: None declared, Sven Plein: None declared, Francesco Del Galdo: None declared, Ai Lyn Tan: None declared, John Biglands: None declared, Maya H Buch Grant/research support from: Pfizer, Roche, and UCB, Consultant of: Pfizer; AbbVie; Eli Lilly; Gilead Sciences, Inc.; Merck-Serono; Sandoz; and Sanofi